Automatic seizure detection in long-term scalp EEG using an adaptive thresholding technique: a validation study for clinical routine - Hopfengärtner, Rüdiger; Kasper, Burkhard; Graf, Wolfgang; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; Stefan, Hermann; Hamer, Hajo (Clinical Neurophysiology, 2014)
In a previous study we proposed a robust method for automatic seizure detection in scalp EEG recordings. The goal of the current study was to validate an improved algorithm in a much larger group of patients in order to show its general applicability in clinical routine.For the detection of seizures we developed an algorithm based on Short Time Fourier Transform, calculating the integrated power in the frequency band 2.5-12 Hz for a multi-channel seizure detection montage referenced against the average of Fz-Cz-Pz. For identification of seizures an adaptive thresholding technique was applied. Complete data sets of each patient were used for analyses for a fixed set of parameters.159 patients (117 temporal-lobe epilepsies (TLE), 35 extra-temporal lobe epilepsies (ETLE), 7 other) were included with a total of 25,278 h of EEG data, 794 seizures were analyzed. The sensitivity was 87.3% and number of false detections per hour (FpH) was 0.22/h. The sensitivity for TLE patients was 89.9% and FpH=0.19/h; for ETLE patients sensitivity was 77.4% and FpH=0.25/h.The seizure detection algorithm provided high values for sensitivity and selectivity for unselected large EEG data sets without a priori assumptions of seizure patterns.The algorithm is a valuable tool for fast and effective screening of long-term scalp EEG recordings.
EVALuna2:22295